Risk factors for the progression of age-related macular degeneration in patients of the Ukrainian population (Ukrainian Journal of Ophthalmology, 2024)
Background: Researchers need to find informative age-related macular degeneration (AMD) criteria which could be used for developing expert systems for the prediction of the course of the disease.Purpose: To evaluate risk factors of AMD progression on the basis of clinical and ophthalmological characteristics in patients of the Ukrainian population.Material and Methods: Totally, 302 eyes (152 patients) with AMD were included in the study. The stage of AMD was determined based on the Age-related Eye Disease Study (AREDS) guidelines. Median patient age (95% confidence interval (CI)) was 71.18 (69.47 – 72.89) years, most (82.9%) patients were of 60 – 85 years, and the percentage of women was 59.9%. Visual acuity, best-corrected visual acuity (BCVA), numbers of small, intermediate and large drusen, presence of retinal pigment epithelium (RPE) changes, subretinal neovascular membranes (SNM), and geographic RPE atrophy were assessed at baseline and at 1 year and 2 years. Statistical analyses were conducted using MedStat and MedCalc v.15.1 (MedCalc Software bvba, Ostende, Belgium) and EZR v.1.64 software (R Foundation for Statistical Computing, Austria).Results: There was a slow but statistically significant reduction in median BCVA (interquartile range (IQR)) from 0.4 (0.1–0.85) at baseline to 0.325 (0.1 – 0.8) (p < 0.001) at 2 years. Over the first year and over the second year, the frequency of RPE changes increased by 6.3% and 10.9%, respectively (p < 0.001), the frequency of SNM detection increased by 13.3% and 21.2%, respectively (p < 0.001), and the frequency of geographic atrophy detection, by 5.7% and 8.0%, respectively (p < 0.001). A multivariate logistic regression model was developed to select four covariates for the risk of AMD progression (the male gender, BCVA, number of small drusen and AREDS category at baseline). The BCVA was negatively associated (р = 0.026; OR = 0.12; 95% CI, 0.03 – 0.60), whereas the number of small drusen was positively associated with the risk of AMD progression (р = 0.009; OR = 1.02; 95% CI, 1.00–1.04). The risk of AMD progression was the highest for eyes with the AREDS category 2 (63.0%, 95% CI, 48.7% – 75.7 %), and the lowest for eyes with the AREDS category 3 (41.2 %, 95% CI, 29.4% – 53.8%, р = 0.049).Conclusion: First, over 24 months, we observed a slow but statistically significant reduction in visual acuity, with an increase in the frequency of RPE changes and detection of SNM and geographic atrophy. Second, a multivariate logistic regression model was developed to select four covariates for the risk of AMD progression (the male gender, BCVA, number of small drusen and AREDS category at baseline). The BCVA was negatively associated, whereas the number of small drusen was positively associated with the risk of AMD progression. Finally, the risk of AMD progression was the highest for eyes with the AREDS category 2, and the lowest for eyes with the AREDS category 3.
Keywords: AREDS; visual acuity; drusen; RPE changes; subretinam neovascular membrane; geographic atrophy; model of disease progression